Sexual health assessments in primary care: a qualitative study of nurse practitioners’ lived experiences - Lloyd, Madeleine (Cultura del cuidado, 2018)
Sexual and reproductive health is a global health, development, and human rights priority. In addition, universal access to sexual and reproductive health is essential. Unfortunately, many nurses feel uncomfortable talking to their patients about sexual health. The purpose of this qualitative study is to illuminate the lived experiences of family nurse practitioners in primary health care when performing sexual health assessments on their adult clients. Using van Manen’s interpretive phenomenological approach, ten interviews were transcribed and analyzed. Understanding the lived experience of these female FNPs, illuminated some of the common experiences when performing a sexual health assessment on their adult clients. Three themes were identified: self-concept, presence, and prudence. There are global nursing implications from understanding these experiences on nursing education, practice, and research.